Are Enchytraeidae (Oligochaeta, Annelida) good indicators of agricultural management practices?. (September 2016) - Pelosi, C.; Römbke, J.
Abstract: Anthropogenic activities and particularly agricultural management may harm soil organisms such as enchytraeids ( Enchytraeidae, Oligochaeta, Annelida ), also known as potworms. These small relatives of earthworms are widely distributed in different soils and land use forms, where they play an important role due to their burrowing activity, their fecal pellet production as well as their transport, ingestion and mixing of mineral and organic soil particles. However, relatively few studies have been performed with these organisms at crop sites – and this widely scattered information has not yet been compiled. Thus, this paper aims (i) to assess the relevance of enchytraeids as indicators of agricultural practices and cropping systems, and (ii) to pinpoint the knowledge gaps and the needs for further research. Out of 250 papers identified in a literature search about 70 were reviewed in detail. Contrasted results and no clear relationships between agricultural practices and the composition and activity of enchytraeid communities have been found in this review, since rarely one factor affecting enchytraeids has been studied alone, meaning that the study context is usually very complex, with several interactions which are difficult to assess. Almost never information about all factors potentially influencing enchytraeids is available and, finally, there are very few studies which had the same aims or designs, making them very difficult to compare even without considering the heterogeneity of agricultural sites in space and time. However, this review concludes that enchytraeids can be considered as indicators of management practices (e.g. soil tillage, inorganic fertilizers) since they are sensitive to changes, both in terms of abundance and species composition. Finally, it is recommended to perform a monitoring program at representative, well documented European sites in which not only the enchytraeid communities but also as many as possible factors influencing them are measured over a period of at least five years. Highlights: Enchytraeids' response to anthropogenic factors can be difficult to identify due to confounding factors. They are sensitive to changes in agricultural practices. They react sensitively to stress such as fertilizer application or tillage. Thus, these annelids can be considered as indicators of agricultural practices.